Performance Evaluation of Lambs Fed Tifton 85 Grass Hay and Concentrate Through LIPE® Marker - Hupp, Adriano Conti; Cóser, Antônio Carlos; Almeida Júnior, Gercílio Alves de; Machado, Thiago Jaccoud; Lemos Hupp, Bárbara do Nascimento; Júnior, Deolindo Stradiotti; Wendling, Ivan Jannotti; Almeida Júnior, Marco Túlio Costa; Morenz, Mirton José Frota (Journal of Agricultural Studies, 2024)
The research was carried out with the aim of evaluate increasing levels of concentrate supplementation on intake and performance of lambs fed Tifton 85 grass hay adopting LIPE® marker technique. Twenty-four weaned and castrated Santa Inês crossbreed lambs with initial body weight (BW) of 20.99 ± 3.62 kg were distributed in four treatments with Tifton 85 hay exclusive or associated with concentrate levels (0.0, 6.6, 13.3 and 20.0 g kg-1 BW d-1), in a completely randomized design with six animals per treatment. The experimental period lasted 98 days, with the first 14 days for animal adaptation to the new environmental conditions, handling and feeding. The diets were fed ad libitum twice a day. Lambs were weighted at each 14 days. Dry matter intake (DMI) was estimated by the technique of Isolated, Purified and Enriched Lignin (LIPE®) while neutral detergent fiber intake (NDFI) and crude protein intake (CPI) were obtained from the content of their fractions present in the diets. There was an increase in DMI and CPI and a similar response in NDFI with the increasing levels of concentrate. The daily liveweight gain per animal showed a linear response when the levels of concentrate were increased and the highest values were observed when 20.0 g kg-1 BW d-1 of concentrate was fed. The increasing levels of concentrate supplementation allowed greater daily and total body weight gains per lamb and there is a consistent relationship between nutrient intakes and performance in the treatments and the LIPE® marker proved to be an efficient technique to evaluate the DMI by lambs.